Midgut serine proteases and alternative host plant utilization in Pieris brassicae L. - Kumar, Rakesh; Bhardwaj, Usha; Kumar, Pawan; Mazumdar-Leighton, Sudeshna (Frontiers in Physiology, 2015)
Pieris brassicae L. is a serious pest of cultivated crucifers in several parts of the world. Larvae of P. brassicae also feed prolifically on garden nasturtium (Tropaeolum majus L., of the family Tropaeolaceae). Proteolytic digestion was studied in larvae feeding on multiple hosts. Fourth instars were collected from cauliflower fields before transfer onto detached, aerial tissues of selected host plants in the lab. Variable levels of midgut serine proteinases were detected in larvae fed on different hosts using protein substrates (casein and recombinant RBCL cloned from cauliflower) and diagnostic, synthetic substrates. Qualitative changes in midgut trypsin activities and quantitative changes in midgut chymotrypsin activities were implicated in physiological adaptation of larvae transferred to T. majus. Midgut proteolytic activities were inhibited to different extents by serine proteinase inhibitors, including putative trypsin inhibitors isolated from herbivore-attacked and herbivore-free leaves of cauliflower (CfTI) and T. majus (TpTI). Transfer of larvae to T. majus significantly influenced feeding parameters but not necessarily when transferred to different tissues of the same host. Results obtained are relevant for devising sustainable pest management strategies, including transgenic approaches using genes encoding plant protease inhibitors.